Paryż w oczach polskich uchodźców u progu Wielkiej Emigracji - Iwańska, Marzena (Acta Universitatis Lodziensis. Folia Historica, 1998)
When a group of Polish emigrants came to Paris after the November Insurrection in the Autumn of 1831, their images of Paris as a splendid place were not confirmed. Poles were offended by street disorder, untidines and lack of space. They were also overpowered with noise, permanent street traffic and crowd. Feeling of solitude and loss was intensified in the face of the world of all-powerful trade and publicity. Polish emigrants were unable to find their place in that great, strange and ruled by power of money city, typical for Western-European civilization. Citizens of French capital were also not especially friendly. Poles experienced really nice moments when they visited respectable Paris monuments and remains of the past.